Application status of standard systems and design schemes of crude oil custody measurement - Shengyang YU; Lumeng JIANG; Cong ZHANG; Ze ZHANG; Xingtao LI; Wei LIU; Shaohua DONG; Dianguo NIU (You-qi chuyun)
With the deep involvement of Chinese oil enterprises in global oil production and the breaking of the integrated management mode of production, transportation and marketing for Chinese oil and gas companies, it's necessary to have a more comprehensive and systematic understanding of crude oil custody measurement. Herein, the five major standard systems of crude oil custody measurement worldwide were sorted out. Comprehensive analysis was conducted for the application of crude oil custody measurement standards in different regions of the world, their interrelationship, and the development of relevant Chinese standards in the oil and gas field. The overall management level concerning the selection of main parameters of custody measurement, the accuracy of relevant instrument and equipment, and their calibration and verification, were analyzed systematically by comparing the requirements of different standard systems in terms of the base condition, oil measurement system, oil test and the calibration of measuring equipment. In addition, four measurement design schemes were summarized by analyzing the design schemes for custody measurement of multiple in-service crude oil pipelines by classification. Further, the quality bank of crude oil was included in the design schemes to improve the measurement management level. Generally, the research results could provide a useful reference for the promotion of relevant oil and gas standards in the emerging region and the design of various custody measurement schemes.